2010
DOI: 10.1186/1423-0127-17-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia induced changes in cholinergic receptor expression in the cerebellum of diabetic rats

Abstract: Glucose homeostasis in humans is an important factor for the functioning of nervous system. Hypoglycemia and hyperglycemia is found to be associated with central and peripheral nerve system dysfunction. Changes in acetylcholine receptors have been implicated in the pathophysiology of many major diseases of the central nervous system (CNS). In the present study we showed the effects of insulin induced hypoglycemia and streptozotocin induced diabetes on the cerebellar cholinergic receptors, GLUT3 and muscle chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…Dopamine D1 receptor expression was downregulated in accordance with the total dopamine receptor decline. However, dopamine D2 receptor expression of cortex and cerebellum were upregulated (2,9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dopamine D1 receptor expression was downregulated in accordance with the total dopamine receptor decline. However, dopamine D2 receptor expression of cortex and cerebellum were upregulated (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…Four groups, classified as control, diabetic, insulin-induced hypoglycemic diabetic, and insulininduced hypoglycemic control rats, were compared. Increased gene expression in the cerebellums of the diabetic hypoglycemic group showed that cerebellar glucose transport impairment is maximal during insulininduced hypoglycemia, leading to neuronal dysfunction (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prolonged influence of mild hypoglycemia on the brain leads to deregulation of many processes in CNS, which underlines the importance of scrupulously avoiding even mild hypoglycemic episodes in patients with DM. Hypoglycemia induces progressive reduction in cerebral glycogen and glucose, which is due to an increase in gene expression of GLUT3, the glucose transporter rather abundant in the brain (Antony et al, 2010b). Alteration of expression of GLUT3 in the cerebral cortex in hypoglycemia is the evidence for impairment of neuronal glucose transport during glucose deprivation.…”
Section: Introductionmentioning
confidence: 99%